AKUNTANSI SYARIAH PADA PEMBIAYAAN PEMILIKAN RUMAH (PPR) DENGAN AKAD MURABAHAH - Zenabia, Tsarina; Fitriyana, Fina; Putri, Yolanda Gusvia; Nuryani, Anum; Rosyati, Tati (LPPM Universitas Pamulang, 2020)
The purpose of the implementation of Community Service entitled